منح مهل الوفاء في دائرة التنفيذ "دراسة مقارنة" - الوتار, سميرة (Latakia University Journal - Economic and Legal Sciences Series, 2015)
<!--[if gte mso 9]> <![endif]--> منح مهل الوفاء في دائرة التنفيذ "دراسة مقارنة" <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; mso-bidi-font-family:Arial;} --> <!--[endif] --> إن سلطة رئيس التنفيذ في إعطاء المدين مهلة للوفاء أو تقسيط الدين تعتبر من المسائل التي اختلف فيها قانوناً وفقهاً وقضاءً، وفي بحثنا هذا وصلنا الى نتيجة مفادها أنه وفي ظل غياب النص الصريح في القانون السوري فإنه يمكن لرئيس دائرة التنفيذ إعطاء المدين مهلة للوفاء بشروط أهمها عدم إلحاق ضرر جسيم بالدائن جراء ذلك، وترك ذلك للسلطة التقديرية لرئيس دائرة التنفيذ خاصة فيما يتعلق بأجل المهلة الممنوحة وحالة المدين التي تستوجب تلك المهلة. The power of executive judge in giving the debtor a time to repay one of the issues that have been argued legally doctrine and judgment. We reached in our research to result that in the absence of the legality item in the Syrian law so, the executive judge can give the debtor a time limit to repay the debt in superior term never cause any damage to the creditor, and leave the judgment power to the executive judge, especially in what related to the time limit that was given and the case of the debtor that incumbent this time.